Women and Diabetes: Preventing Heart Disease in a New Era of Therapies - Giuseppe Galati (Radcliffe Medical Media, 2021)
Despite major advances in cardiovascular research over the past decade, women with type 2 diabetes have a high risk of cardiovascular events. Several factors contribute to the poor prognosis for women, including higher levels of frailty and comorbidities, but their cardiovascular risk is underestimated and there is suboptimal implementation and uptitration of new evidence-based therapies, leading to high morbidity and mortality. Recent studies highlight the need for better management of diabetes in women that can be pursued and achieved in light of recent results from randomised controlled trials demonstrating evidence of the benefits of new therapeutic strategies in improving cardiovascular outcomes and quality of life of women covering the entire cardiovascular continuum. This review critically discusses the multiple benefits for women of new pharmacological treatments, such as glucagon-like peptide-1 receptor agonists, sodium–glucose cotransporter type 2 inhibitors (SGLT2i), proprotein convertase subtilisin/kexin type 9 inhibitors, inclisiran, icosapent ethyl and bempedoic acid in preventing cardiovascular events, and treatments, such as angiotensin receptor neprilysin inhibitors, SGLT2i, vericiguat and omecamtiv mecarbil, for preventing heart failure.